Personalized chemotherapy selection for patients with triple-negative breast cancer using deep learning - Yang, Xinyi; Vladmirovich, Reshetov Iogr; Georgievna, Poltavskaya Maria; Sergeevna, Agakina Yulia; He, Mingze; Zeng, Zitong; Qiang, Yinpeng; Cao, Yu; Sergeevich, Kulikov Timur (Frontiers in Medicine, 2024)
Background: There are potential uncertainties and overtreatment existing in adjuvant chemotherapy for triple negative breast cancer (TNBC) patients. Objectives: To explore the performance of deep learning (DL) models in personalized chemotherapy selection and to quantify the impact of baseline characteristics on treatment efficacy. Methods: Patients who received treatment recommended by models were compared with those who did not. Overall survival for treatment according to model recommendations was the primary outcome. To mitigate bias, inverse probability treatment weighting (IPTW) was employed. A mixed effect multivariate linear regression was employed to visualize the influence of certain baseline features of patients on chemotherapy selection. Results: A total of 10,070 female TNBC patients met the inclusion criteria. Treatment according to Self-Normalizing Balanced individual treatment effect for survival data (SNB) model recommendations was associated with a survival benefit (IPTW-adjusted hazard ratio: 0.53, 95% CI, 0.32-8.60; IPTW-adjusted risk difference: 12.90, 95% CI, 6.99-19.01; IPTW-adjusted the difference in restricted mean survival time: 5.54, 95% CI, 1.36-8.61), which surpassed other models and National Comprehensive Cancer Network guidelines. No survival benefit for chemotherapy was seen for patients not recommended to receive this treatment. SNB predicted older patients with larger tumors and more positive lymph nodes is the optimal candidates for chemotherapy. Conclusions: These findings suggest that SNB model may identify patients with TNBC who could benefit from chemotherapy. This novel analytical approach may provide debiased individual survival information and treatment recommendations. Further research is required to validate these models in clinical settings with more features and outcome measurements.